Technical tactical considerations liver surgery - Torterolo, Edgardo; Silva, Celso; Cidade, Luis; Czarnevicz, Daniel; Leites, Alejandro; Vergara, Mirtha; Aizen, Bernardo; Ferreira, Carlos; Bergalli, Luis; Fernández, Miguel; Kaitazzof, Pedro; Perdomo, Susana; et al. (Cirugía del Uruguay, 1994)
As regards 155 hepatic resections, technico-tactical aspects are considered. These include mainly the determination of risk factors for resection, the election of patients and functional and anatomica/ counterindications. Considerations are made on patient preparation as well as on details of surgical technique; intraoperative echography stands out in decision-making. Special emphasis is made on clamping and its consequences, pointing out the advantages of sectorial vascular isolation of the /iver.